2019
DOI: 10.1021/acsami.9b05531
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Silk Coatings Reduce the Adhesion of Staphylococcus aureus while Supporting Growth of Osteoblast-like Cells

Abstract: Orthopedic and dental implants are associated with a substantial risk of failure due to biomaterial-associated infections and poor osseointegration. To prevent such outcomes, a coating can be applied on the implant to ideally both reduce the risk of bacterial adhesion and support establishment of osteoblasts. We present a strategy to construct dual-functional silk coatings with such properties. Silk coatings were made from a recombinant partial spider silk protein either alone (silk wt ) or fused with a cell-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 38 publications
(80 reference statements)
1
42
0
Order By: Relevance
“…Titanium has shown excellent results for cell adhesion and proliferation, which is essential to favor greater cell anchorage, facilitating osteointegration [13,32,33]. The present study demonstrated that coated and uncoated titanium samples showed a good adhesion of human osteoblasts on their surfaces, and the cell coverage area was similar in both the coated and uncoated samples.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Titanium has shown excellent results for cell adhesion and proliferation, which is essential to favor greater cell anchorage, facilitating osteointegration [13,32,33]. The present study demonstrated that coated and uncoated titanium samples showed a good adhesion of human osteoblasts on their surfaces, and the cell coverage area was similar in both the coated and uncoated samples.…”
Section: Discussionsupporting
confidence: 57%
“…The biocompatibility or the cell viability can be evaluated by the direct interaction between the material surface and the cells [32,33], and live/dead studies exhibit good cell biocompatibility. The quantification of cell counts by ImageJ as fields of view (Figure 3) verified that the cell viability of the implants was not less than but similar to the cell viability of the uncoated implants.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, two endolysins, named PlySs2 and PlySs9 as derivatives from prophages in the genomes of the porcine pathogen Streptococcus suis , were characterized as potential antimicrobial compounds against bovine mastitis-causing S. uberis . PlySs2 is known to display broad lytic activity against several streptococci i.e., Streptococcus equi , Streptococcus agalactiae, Streptococcus dysgalactiae , Streptococcus pyogenes , Streptococcus sanguinis , Streptococcus pneumoniae and group E streptococci [ 32 , 33 , 34 ]. In addition, its lytic activity was confirmed in an animal model showing eradication of S. suis from murine nasal mucosa with a > 4 log reduction [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…After 28 days, complete fracture healing was observed for this group (Windolf et al 2014). Besides lysostaphin, PlySs2 and SAL-1 were immobilized on self-assembling spider silk proteins, resulting in an effective antistaphylococcal fibre (Nileb€ ack et al 2019;Seijsing et al 2020). In addition, one can target biofilm formation specifically combining lysins with matrix-degrading enzymes such as Dispersin B (Seijsing et al 2020).…”
Section: Lysin Coatings For Implanted Devices and Cathetersmentioning
confidence: 99%